In-season strength training in elite junior swimmers: the role of the low-volume, high-velocity training on swimming performance - Marques, M. C.; Yáñez-García, J. M.; Marinho, D. A.; González-Badillo, J. J.; Rodríguez-Rosell, D. (Journal of Human Kinetics, 2020)
The aim of this study was to analyze the effect of long-term combined strength training (ST) and plyometrics on strength, power and swimming performances in elite junior swimmers during a competitive season. Ten elite junior swimmers (5 women and 5 men) completed the study (age: 16.6 ± 0.7 years; mass: 62.2 ± 5.4 kg; stature: 1.70 ± 0.07 m). The participants trained twice a week during 20 weeks. The ST program consisted of upper- and lower limbs exercises with low loads and low volume, lifting the load at maximal intended velocity. The effect of the training protocol was assessed using the 1RM in the full squat (SQ) and bench press (BP), jump height (CMJ), the maximal number of repetitions completed in the pull-up (PU) exercise and time during 50-m freestyle. Training program resulted in significant improvements in CMJ (12.1%, ES: 0.57), maximal dynamic strength in the SQ (16.4%, ES: 0.46) and BP (12.1%, ES: 0.34) exercises, the maximum number of repetitions completed during the PU test (90.7%, ES: 0.57) and swimming performance (-3.9%, ES: 0.45). There were no significant differences between both genders. The relative changes in swimming performance showed significant relationship with the relative changes in 1RM of SQ for pooled data (r=-0.66, p<0.05) and the relative changes in the PU exercise in female swimmers (r=-0.99, p<0.05). Therefore, coaches and strength and conditioning professionals should consider including in-season dry-land ST programs within the training routine in order to obtain further improvements in swimming performance.